OPTIMIZING TEACHER QUALITY THROUGH INNOVATIVE EDUCATIONAL LEADERSHIP: A STUDY OF PDCA-BASED TQM STRATEGY BY SCHOOL PRINCIPALS - Elistatia, Usi; Bedi, Fisman; Fitri, Tin Amalia (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
The quality of education is closely related to the quality of teaching staff at all levels of education. Teachers play a central role in shaping a superior and competitive generation. This research aims to explore the strategies of school principals to improve the quality of teachers and other education personnel. To better understand the actions taken by school principals to optimize the quality of teaching through the implementation of Total Quality Management based on the Plan-Do-Check-Act (PDCA) cycle, this study uses a qualitative approach with a case study methodology. Based on the findings of the research, Insan principals have implemented a structured and sustainable approach to improving teacher quality through various strategies, including selective teacher recruitment, teacher personality, and competency development, involvement in training and workshops, and awarding outstanding teachers. The implementation of the PDCA cycle in each strategic step allows school principals to monitor, evaluate, and make necessary improvements on a regular basis. The implications of this study enrich the study of education quality management in the form of learning quality, teacher effectiveness, and a culture of continuous improvement in schools. In addition, strategies (Palan, Do, Check, and Act). Then provide recommendations to education policymakers, both at the school level, the education office, and the government.